An Adaptive OFDM Detection Strategy for Range and Doppler Spread Targets in Non-Gaussian Clutter - Zhen Du (IEEE Access, 2018)
Orthogonal frequency division multiplexing (OFDM) radar can obtain higher target detection performance than traditional single carrier frequency radar due to simultaneously multiple frequency measurements. Meanwhile, the detection performance can be further improved by utilizing both the range and Doppler distribution information for extended targets. In this paper, an OFDM detection strategy for range and Doppler spread targets in non-Gaussian clutter is proposed, which comprises a new generalized likelihood ratio test (GLRT) detector and an adaptive waveform design method. The deduced GLRT detector is an asymptotically optimal detector and has a constant false alarm rate property. Comparisons show that the GLRT detector outperforms other existed detectors, which use the range-only spread model or the point-like target model. Furthermore, by optimizing the transmitted weights corresponding to different subcarriers of the OFDM signal, an approximate 2-dB output signal-to-clutter ratio improvement is achieved, which benefits the target detection with a cognitive manner.